The Effect of Moral Liability, the Effectiveness of Tax Socialization, Aspects of Tax Law Enforcement and The Digitalization of Tax Services on Taxpayer Compliance with Nationalism as A Moderation Variable - Rio Johan Putra; Deri Deri (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
This study aims to determine the effect of variables on moral obligation, effectiveness of tax socialization, aspects of tax law enforcement, and digitization of tax services on taxpayer compliance by moderating nationalism. The research method used in this research is a quantitative research method with primary data obtained from questionnaire data which is measured using a Likert scale. Ease of carrying out tax obligations has been optimized by internal parties such as digitalization in tax services. However, this is still not effective in increasing taxpayer compliance. People prefer to come directly to the nearest KPP, because they think that directly coming to the KPP is easier to ask something about taxes that they do not understand. The researcher suggests that DPs should conduct counseling focused on understanding the basics of the process of modernizing or digitizing tax administration. The DGT is advised to consistently make efforts to bring its tax services closer, for example by using a mobile tax car. This study uses the variable of nationalism as a moderator in the factors that influence taxpayer compliance which has not been done by other researchers.